Pengaruh Penggunaan Media Digital Aplikasi Wattpad terhadap Kemampuan Membaca Siswa SMA Budisatrya dalam Pembelajaran Bahasa Indonesia: The Influence of Using the Wattpad Application Digital Media on the Reading Ability of Budisatrya High School Students in Indonesian Language Learning - Winda Vita Puri Dalimunthe; Edi Saputra (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the impact of using the Wattpad application as a digital medium on students' reading skills at Budisatrya High School in Indonesian language lessons. The main reason for conducting this research in the context of Indonesian language learning and the urgency of innovative teaching methods due to the characteristics of the digital generation is the low interest of students in reading activities. This study applied a quasi-experimental design and quantitative methodology. The research subjects were divided into two groups: a control group implementing traditional techniques and an experimental group utilizing Wattpad as a learning aid. The difference between the average pre-test score of 41.5 and 56.6 on the post-test indicated that the reading skills of the experimental group had improved significantly. Conversely, the control group only experienced an increase from an average of 37.5 to 43.5. The t-test results showed a significance value of 0.009 (<0.05), indicating a statistically significant difference between the two groups. Normality and homogeneity tests also proved that the data met the parameters for the t-test. In addition, the survey results showed that children were more motivated and interested in using Wattpad because the content was appropriate for their age and interests. According to the study's findings, using Wattpad as a digital tool can help children become more skilled readers and develop an interest in digital literacy. Educators should incorporate digital media into their lessons to make learning more engaging and relevant.